Management arrangements for accommodating nonrice crops in rice-based irrigation systems. proceedings of the First Progress Review and Coordination Workshop of the Research Network on Irrigation Management for Crop Diversification in Rice-Based Systems (IMCD), held in Quezon City, the Philippines, 10-14 December 1990 - Miranda, S.M.; Maglinao, Amado R. (International Irrigation Management Institute, 1992)
The country reports presented at the workshop focused on the experience of the different countries on irrigation management for rice-based cropping as these relate to planning, implementation, monitoring an evaluation both at the system and farm levels. The special papers presented discussed research and policy issues on irrigation management for crop diversification.